Problems of judicial practice in disputes related to counter claims - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article the problems of judicial practice are analysed during permission of homogeneous claims in return, that is examined by the economic courts of Ukraine. This article examines the challenges that arise in dealing litigation related with counter uniform requirements, ambiguity practical usage of this institute, adopting different meaning judgments which are considered Commercial courts of Ukraine. Actuality is that The Commercial courts of Ukraine considering disputes between entities related with counter uniform requirements do not equally apply the same substantive and procedural law therefore adopt different meaning judicial acts in similar legal relationships. Particular difficulties with enrollment counter uniform requirements arise when in one of the creditors initiated bankruptcy. Ambiguity practical application of this institute is due to the fact that the Ukraine legislation does not contain an exhaustive list of cases where enrollment counter uniform requirements is unacceptable. The Civil and Commercial Law of Ukraine indicated the possibility of establishing cases where enrollment uniform requirements is unlawful.